PENGARUH MACAM MEDIA TERHADAP PERTUMBUHAN BIBIT MENTIMUN (Cucumis sativus, L.) HASIL PENYUSUAN DENGAN WALUH (Cucurbita moschata) - Arfi Erwindi; Murti Astiningrum; Historiawati Historiawati (JURNAL VIGOR, 2017)
A research to study the effect of the use of growing media on the growth a seedlings of cucumber (Cucumis sativus, L.) treated approach grafting with pumpkin (Cucurbita moschata).The research had been conducted on December 5, 2014 until January 17, 2015 in the village of Sangrahan, District Kranggan,Temanggung Regency. Altitude ± 600 m. This study used factorial experiment (2x3) arranged in completely randomized design (CRD) with three replications. The first factor: is day of grafting 10, 15, and 20 days aftersowing. The second factor  is growing media cocopeat and husk. The analysis showed that grafting on 15 days led to higher seedling , highest number of successful approach grafting, fresh weight and dry weight of seedlings uper part, as well as the highest root fresh weight. Cocopeat cause the highest number of successful approach grafting, fresh weighting and dry weight of seedlings uper part and higher rooting fresh weight. Grafting on difrent days and grown on different media responded regularly on observed parameters.